Digging The Local Knowledge: Using Video-Camera to Engage School Children in Maritime Culture - Gunawan, Gunawan (KOMUNITAS: International Journal of Indonesian Society and Culture, 2020)
In the current era of globalism penetration, many local communities face challenge especially in the existence of their local knowledge and wisdom. The younger generation began to move away from various locality systems as a result of the intervention of industrialism, modern education and global information exposure. Therefore, an effort to generate local knowledge around the lives of young people is needed so that their lives are not uprooted from the roots of cultural history and local wealth which is actually still very much needed in facing life's challenges. This article is the result of a research conducted on the community of Banyutowo Village, Dukuhseti Subdistrict, Pati Regency in an effort to develop local potential and knowledge through a community school for fishermen's children. The purpose of this article is to explain how maritime knowledge can be developed in fishermen's children through film designed by the children themselves. The study uses qualitative methods with a participatory approach and action research. The results of the study show that using camera to make films about maritime localities in the village directly involving the children provides space for them to know, feel, and reflect themselves in the maritime knowledge of their village communities.